Growth of Knowledge and Education in Nepal (TULSSAA Journal, 2025)
Knowledge and education are critical drivers of a nation's progress. Nepal, with its rich cultural and historical legacy, has seen significant developments in the field of education, research, and innovation. This paper explores the evolution of knowledge in Nepal, from traditional learning systems to modern education frameworks, research advancements, and the challenges faced in this domain. It also highlights the role of digital transformation and policy reforms in shaping the country's knowledge ecosystem. The study relies on various scholarly sources, government reports, and institutional research to provide a comprehensive view of Nepal’s educational landscape.